2014
DOI: 10.4172/2157-7439.1000225
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Silver Nanoparticles on the Blood-Brain and the Blood-Cerebrospinal Fluid Barrier in vitro

Abstract: The use of silver nanoparticles in medical and consumer products such as wound dressings, clothing and cosmetic has increased significantly in recent years. Still, the influence of these particles on our health and especially on our brain, has not been examined adequately up to now. We studied the influence of AgEO-(Ethylene Oxide) and AgCitrate-Nanoparticles (NPs) on the protective barriers of the brain, namely the blood-brain barrier (BBB) and the blood-cerebrospinal fluid (blood-CSF) barrier in vitro. The N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 50 publications
(71 reference statements)
2
12
0
Order By: Relevance
“…The overall low and size‐dependent permeability to FITC‐dextrans further confirmed the barrier integrity of the BBB constructs in our model. Remarkably, we achieved extremely low permeabilities to FITC‐dextrans that were comparable to previously reported in vivo values (Shi et al, ; Yuan et al, ) and the in vitro data from transwell models with high TEER values (Cramer, ; Matthes et al, ). Our results were around two to three orders of magnitude lower than those reported from existing microfluidic BBB models (Booth and Kim, ).…”
Section: Resultssupporting
confidence: 89%
“…The overall low and size‐dependent permeability to FITC‐dextrans further confirmed the barrier integrity of the BBB constructs in our model. Remarkably, we achieved extremely low permeabilities to FITC‐dextrans that were comparable to previously reported in vivo values (Shi et al, ; Yuan et al, ) and the in vitro data from transwell models with high TEER values (Cramer, ; Matthes et al, ). Our results were around two to three orders of magnitude lower than those reported from existing microfluidic BBB models (Booth and Kim, ).…”
Section: Resultssupporting
confidence: 89%
“…An earlier study by Trickler et al reported that AgNPs increased the BBB permeability in primary rat brain endothelial cells, and induced a size-dependent pro-inflammatory response by secreting PGE2, TNF-α and Il-1β [58]. Cramer et al studied the effect of AgNPs’ surface coatings (citrate and ethylene oxide (EO) on neurotoxicity of primary porcine brain capillary endothelial cells (PBCECs) [219]. Neutral red uptake assay revealed that cell viability decreased markedly from 100% to 58% and 71%, respectively, upon exposure to EO-AgNPs and CT-AgNPs at 50 μg/mL.…”
Section: In Vitro Cell Cultivationmentioning
confidence: 99%
“…From in vitro cell cultivation, AgNPs increased the permeability of tight junctions of brain endothelial cells [219]. The ICP-MS measurements of in vivo animal model showed the presence of a small amount of AgNPs in the mice brain [229,232,234].…”
Section: In Vivo Animal Modelmentioning
confidence: 99%
“…24 Several studies have demonstrated that Ag-NPs can enter the CNS 25 and induce brain edema and neurotoxicity. 10,11,[26][27][28][29] Our previous studies showed that Ag-NPS and/or released Ag ions crossed the BBB and subsequently caused damage to astrocytes and neurons. 23 Cadherin and claudin expression were slightly changed in the Ag-NPS-exposure group, and astrocyte swelling was the most significant change after a 2-week gastrointestinal exposure to 1 mg/kg or 10 mg/kg of Ag-NPS in rats.…”
Section: Discussionmentioning
confidence: 99%